Comparative Study of Nutritional Value of Wheat, Maize, Sorghum, Millet, and Fonio: Some Cereals Commonly Consumed in Côte d’Ivoire - Jocelyne, Robet Emilie; Béhiblo, Konan; Ernest, Amoikon Kouakou (European Scientific Journal, ESJ, 2020)
This paper focuses on providing a useful database for the decisionmakers for adequate food security policy. It involves making a comparative study of the nutritional values of wheat, maize, sorghum, millet and fonio, which are the five cereals largely consumed in Côte d’Ivoire. In conducting this study, physicochemical analysis were performed. The results reveal that wheat, maize, sorghum, millet, and fonio have an acidic pH. These cereals contain relatively little amount of water and a large proportion of fibers. Carbohydratesrepresent the highest proportion of the dry matter of the cereals, while maize contains the most important rate. Maize, sorghum, and millet contain more lipids. Wheat, maize, and millet have lower ashes. Wheat and millet contain more proteins. Millet, sorghum, and fonio are the richest cereals in iron. Wheat is rich in calcium but has a lower content of potassium, phosphorus, and Magnesium. Fonio is rich in zinc. Cereals are rich in phytochemical compounds such as phenolic acid, flavonoids, and tannins. It is also important to take into cognizance the presence of antinutritional compounds such as phytates and oxalates. The results show that all the cereals studied represent potential sources of energy in Ivorians food but also has significant sources of fibers and minerals.